Hourly storm characteristics along the U.S. West Coast: Role of atmospheric rivers in extreme precipitation. Issue 13 (3rd July 2017) - Lamjiri, M. A.; Dettinger, M. D.; Ralph, F. M.; Guan, Bin
Abstract: Gridded hourly precipitation observations over the conterminous U.S., from 1948 to 2002, are analyzed to determine climatological characteristics of storm precipitation totals. Despite generally lower hourly intensities, precipitation totals along the U.S. West Coast (USWC) are comparable to those in southeast U.S. (SEUS). Storm durations, more so than hourly intensities, strongly modulate precipitation‐total variability over the USWC, where the correlation coefficients between storm durations and storm totals range from 0.7 to 0.9. Atmospheric rivers (ARs) contribute 30–50% of annual precipitation on the USWC and make such large contributions to extreme storms that 60–100% of the most extreme storms, i.e., storms with precipitation‐total return intervals longer than 2 years, are associated with ARs. These extreme storm totals are more strongly tied to storm durations than to storm hourly or average intensities, emphasizing the importance of AR persistence to extreme storms on the USWC. Key Points: On average, storms in the U.S. West Coast (USWC) and southeast U.S. (SEUS) have the largest precipitation totals in the conterminous U.S. Precipitation totals are more strongly correlated with storm duration in the USWC and with storm maximum intensity in the SEUS The most extreme USWC storms are most often the most persistent atmospheric rivers rather than high‐intensity ones